Relationship between growth traits and yield formation in Indica-type rice crop - Maqueira López, Lazaro Alberto (2019)
Introduction. Climatic variation is one of the causes for the decrease in yield and its variability in Indica-type rice (Oryza sativa L.). This evidences the necessity of the study of the interaction of meteorological variables with the behavior of rice cultivars, to establish the base of management of the harvest and increase of the yield. Objective. The objective of the present study was to relate the yield of rice with variables of plant growth. Materials and methods. Four rice cultivars were planted in the “dry” season of December 2004, February 2005 and January 2006, and in the rainy season of March 2006, April 2008 and 2009, in Los Palacios, Pinar del Río province, Cuba. The yield and its components, the dynamics of plant growth (LAI and dry matter), the variation of the dry matter of the internodes, peduncle, flag leaf, leaf and leaf sheath during the grain filling phase were evaluated the panicle growth in addition to the meteorological data. A multivariate analysis was used to relate the performance to the characteristics of the plants evaluated. Results. The yield was higher in the “dry” season and to obtain higher yields, the growth dynamics of the plant and the variation of the dry matter of the third internode during the grain filling were important. In both seasons, different source-sink relationships were established and these situations depended mainly on the temperature regime at which the plants were subjected. Conclusion. Breeders, in order to increase potencial yields, may fows their atttention in grow traits during vegetative stages.